2020
DOI: 10.1002/bit.27210
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Saccharomyces cerevisiae to industrially relevant conditions: Slow growth, low pH, and high CO2 levels

Abstract: Engineered strains of Saccharomyces cerevisiae are used for industrial production of succinic acid. Optimal process conditions for dicarboxylic-acid yield and recovery include slow growth, low pH, and high CO 2 . To quantify and understand how these process parameters affect yeast physiology, this study investigates individual and combined impacts of low pH (3.0) and high CO 2 (50%) on slow-growing chemostat and retentostat cultures of the reference strain S. cerevisiae CEN.PK113-7D. Combined exposure to low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 87 publications
3
18
2
Order By: Relevance
“…However, long-term cultivation of S. cerevisiae at the near-zero growth rate in retentostat cultures has been reported to result in accumulation of nonviable, nonproducing cells (Boender et al, 2009;Vos et al, 2016). A previous study with the nonproducing laboratory reference strain CEN.PK113-7D (Hakkaart et al, 2020) showed that, at pH of 3, the specific death rates (k d ) in glucose-and ammonium-limited retentostat cultures (0.0039 ± 0.0005 and 0.0030 ± 0.0004 h −1 , respectively) were approximately eightfold higher than in corresponding cultures grown at pH of 5. However, cultivation of the reference strain at near-zero growth rate as such did not result in an increased k d , because the death rates in glucoseand ammonium-limited retentostat cultures performed at pH of 3 were respectively two and tenfold lower than in corresponding F I G U R E 6 Intracellular levels of the TCA cycle metabolites (a-f) and mass action ratio's of fumarase and aconitase (g,h) during aerobic, ammonium-limited retentostat cultivation of SUC632.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, long-term cultivation of S. cerevisiae at the near-zero growth rate in retentostat cultures has been reported to result in accumulation of nonviable, nonproducing cells (Boender et al, 2009;Vos et al, 2016). A previous study with the nonproducing laboratory reference strain CEN.PK113-7D (Hakkaart et al, 2020) showed that, at pH of 3, the specific death rates (k d ) in glucose-and ammonium-limited retentostat cultures (0.0039 ± 0.0005 and 0.0030 ± 0.0004 h −1 , respectively) were approximately eightfold higher than in corresponding cultures grown at pH of 5. However, cultivation of the reference strain at near-zero growth rate as such did not result in an increased k d , because the death rates in glucoseand ammonium-limited retentostat cultures performed at pH of 3 were respectively two and tenfold lower than in corresponding F I G U R E 6 Intracellular levels of the TCA cycle metabolites (a-f) and mass action ratio's of fumarase and aconitase (g,h) during aerobic, ammonium-limited retentostat cultivation of SUC632.…”
Section: Discussionmentioning
confidence: 99%
“…Data represent the averages and standard errors of measurements from duplicate cultures. αKG, α-ketoglutarate; Cit, citrate; Fum, fumarate; IsoCit, isocitrate; Mal, Malate; Suc, succinic acid; TCA, tricarboxylic acid [Color figure can be viewed at wileyonlinelibrary.com] chemostat cultures grown at a specific growth rate of 0.025 h −1 at pH of 3 (Hakkaart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomass concentrations were determined by filtering duplicate, exact volumes of culture broth (5 mL), over pre-dried Supor 47 membrane filters with a 0.45 μm pore size, washed and then dried in a microwave oven for 20 min at 360 W and weighed again (Pall Laboratory, Port Washington, NY, United States) as described by Postma et al (1989) . Extracellular metabolites of the cultures were obtained by centrifuging culture samples (10 min at 3500 g) of which the supernatant was analyzed by HPLC as described previously by Hakkaart et al (2020) .…”
Section: Methodsmentioning
confidence: 99%